Postoperative ileus: strategies for reduction - James Lubawski; Theodore Saclarides (Dove Medical Press, 2008)
James Lubawski, Theodore SaclaridesSection of Colon and Rectal Surgery, Rush University Medical Center, Chicago, IL, USAAbstract: Postoperative Ileus (POI) is a frequent, frustrating occurrence for patients and surgeons after abdominal surgery. Despite significant research investigating how to reduce this multi-factorial phenomenon, a single strategy has not been shown to reduce POI’s significant effects on length of stay (LOS) and hospital costs. Perhaps the most significant cause of POI is the use of narcotics for analgesia. Strategies that target inflammation and pain reduction such as NSAID use, epidural analgesia, and laparoscopic techniques will reduce POI but are accompanied by a simultaneous reduction in opioid use. Pharmacologic means of stimulating gut motility have not shown a positive effect, and the routine use of nasogastric tubes only increases morbidity. Recent multi-site phase III trials with alvimopan, a peripherally acting mu-antagonist, have shown significant reductions in POI and LOS by 12 and 16 hours, respectively, by blunting the effects of narcotics on gut motility while sparing centrally mediated analgesia. Use of alvimopan, along with a multi-modal postoperative treatment plan involving early ambulation, feeding, and avoiding nasogastric tubes, will likely be the crux of POI treatment and prevention.Keywords: postoperative ileus, alvimopan, abdominal surgery